Influence of health literacy on health outcomes of different social strata—— an empirical study based on the data of China's health literacy investigation - Huifang Yu; Siwen Sun; Jie Ling; Haixiao Chen; Guilin Liu (International Journal for Equity in Health, 2023)
Abstract Background Health literacy has always been considered as an important factor to promote people's health, but does it have a significant effect on health across all social strata and especially lower social strata? This study aims to analyze the influences of health literacy on health outcomes of different social strata, and then infer whether improving health literacy can reduce health disparities among different social strata. Methods Utilizing health literacy monitoring data from a city in Zhejiang Province in 2020, the samples are divided into three social strata according to the socioeconomic status score: low, middle and high social stratum, to compare whether there are significant differences in health outcomes between population with lower and higher health literacy among different social strata. In the strata with significant differences, control the confounding factors to further verify the influence of health literacy on health outcomes. Results In low and middle social strata, there are significant differences between population with lower and higher health literacy, when considering the two types of health outcomes (chronic diseases and self-rated health), but in high social stratum, this difference is not significant. After controlling the relevant variables, the influence of health literacy on the prevalence of chronic diseases is statistically significant only in low social stratum, and the health literacy is negatively correlated with the prevalence of chronic diseases(OR = 0.722, P = 0.022). In addition, there are statistical significances for positive impact of health literacy on self-rated health in both low and middle social strata (OR = 1.285, P = 0.047; OR = 1.401, P = 0.023). Conclusion Compared with high social stratum, the influence of health literacy on health outcomes of low social stratum (chronic diseases) or both middle and low social strata (self-rated health) is more significant, and both are to improve the health outcomes. This finding suggests that improving residents' health literacy may be an effective way to alleviate the health disparities among different social strata.